Work piles - columns with soil under constant influence of vertical and cyclically approximated horizontal loads - Barchukova Tetіana (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article describes an experimental study aimed at identifying common patterns of joint work of piles - columns with soil with vertical and cyclically applied horizontal loads. The study examines the deformation processes occurring in the soil. At any pressure value, soil deformations can be divided into two groups, which are restored (elastic) and residual. When the pressure is less than the structural strength, elastic deformations appear. With a pressure of greater structural strength, elastic and residual deformations appear. Elastic deformations appear throughout the depth, residual deformations develop in the depth of the deformation zone, where the stress exceeds the structural strength of the soil. After removing the load, the elastic deformation disappears, and the residual remains. The lower limit of the residual strain zone is at a depth, where the stresses from the load transmitted by the column of piles below its base are balanced by the structural strength of the soil.